Bunk, What in the World Art Thou? - Nasrallah, Nawal (Petits Propos Culinaires, 2021)
Because dining in the Arab world in medieval times involved sharing communal dishes eaten with hands, the routine of washing them before and after the meals was obligatory. This article explores what might constitute one such cleansing agent, known as bunk.